Inquietações sociofilosóficas sobre corpos travestis - Alves, Mamede Wilson Simas (2022)
Brazil is the country which most consumes transvestite pornography and also the one which commits most violence against these people. In this sense, it is possible to notice the dichotomy between the trans individuals and society, in which they are at once desired and extermined. In order to problematize this dichotomy, I question how the construction of the transvestite's body occurs and the places historically destined for her in society, strongly linked to prostitution, as well as her possibility of occupying new spaces. In this Master’s thesis, I seek to understand in the first chapter the historical construction of these subjects – their name, body, and identity – who move in the tension of this reality, confronted from the desire and the need to seek rights in the face of the violence that trans folks have been repeatedly subjected to, linked to the marginalized social place that has been assigned to them over time and whose questioning was possible from the entry into social movements, such as feminist groups and directed to homosexual rights. The transvestite becomes a political subject based on the language that her body represents, creating boundaries of socialization wherever she goes, breaking with the norm of sex and gender, which can be thought through the eyes of Judith Butler, whose insightful production deals with the exclusionary way that certain subjects suffer from the heterosexual matrix, making them abject beings, a discussion guided in the second chapter. In order to try to explain the transvestite gender identity, I use genealogical critique as a methodology, in an attempt to understand the origin and cause of the categories of identity, discourses, practices and effects that come from the institutions that build the path that the transvestite is today. I conclude this thesis by commenting on the interview (2018) carried out by Linn da Quebrada, a transvestite, black and peripheral, who also went through prostitution, with Judith Butler, one of the greatest producers of philosophical content on gender issues, weaving possibilities of other places and looks for these folks: “I would never imagine a transvestite interviewing a philosopher.”